Study of the Influence of Mushika Racing Car Rear Wing Variations on Traction Potential by Using CFD Program - EZRA TAKWARIF - NIM: 13111061 , JOEL
This undergraduate final project has the purpose to increase the aerodynamics performance of the existing Mushika M-02 race car. Mushika is a race car designed by students of the Mechanical Engineering Department of ITB that was intended to participate in the FSAE competition. Mushika race car is researched in this scientific paper with the purpose increasing the acceleration potential. From the existing Mushika race car testing, the traction resulted from the wheel is not sufficient. Aerodynamically, this traction can be increased by focusing the geometry of the rear car wing and giving the effort in increasing the ratio of downforce per drag generated by the Mushika race car. Performance increasing through research upon car wing is done by using the program Computational Fluid Dynamics or CFD with Ansys Fluent. Ansys Fluent does the analysis of the Mushika race car CFD by using the Inventor program. From the results of simulations and the calculation of the traction, it is concluded that the rear wing of the Mushika race car has aerodynamics effect that increases the wheel traction. This increase can be achieved by raising the angle of attack until certain limit and enlarging the size of the rear wing itself. Despite of the increase, the analytical result of the traction indicates that the aerodynamic forces generated is below the desired wheel traction.